Evidence from Indonesia: improving practical skills in media broadcasting through project-based learning - Winarko, Hilarius Bambang; Andreansyah, Samuel; Warokka, Ari (Jurnal Studi Komunikasi, 2025)
While Project-Based Learning (PBL) is widely recognised as an effective pedagogical approach in media education, significant gaps remain in understanding its implementation and impact in developing country contexts. Challenges such as resource constraints, industry-academia disconnects, and varying institutional capacities may limit PBL's effectiveness in preparing media broadcasting students for professional careers. This study examined these issues through a longitudinal investigation of PBL implementation at an Indonesian private university's media broadcasting laboratories. Using quantitative research analysis of student performance data across five core courses, the study reveals that PBL significantly enhances practical competencies when properly supported. Key findings show more than 60% of participants achieved top grades, with strong correlations between PBL participation and skill development. The study identifies industry-aligned projects and structured mentorship as critical success factors, while highlighting persistent challenges related to equipment access and time constraints. These results demonstrate PBL's potential to bridge the gap between academic training and industry needs in resource-constrained environments. The findings recommend that strategic investments in laboratory infrastructure, faculty development, and industry partnerships could help overcome implementation barriers and maximise PBL's benefits for media education in developing contexts.